Congenital Aortic Valve Stenosis - Singh, Gautam K. (Children (Basel), 2019)
Aortic valve stenosis in children is a congenital heart defect that causes fixed form of hemodynamically significant left ventricular outflow tract obstruction with progressive course. Neonates and young infants who have aortic valve stenosis, usually develop congestive heart failure. Children and adolescents who have aortic valve stenosis, are mostly asymptomatic, although they may carry a small but significant risk of sudden death. Transcatheter or surgical intervention is indicated for symptomatic patients or those with moderate to severe left ventricular outflow tract obstruction. Many may need reintervention.